On-chip polariton generation using an embedded nanograting microring circuit - N. Pornsuwancharoen; P. Youplao; I.S. Amiri; J. Ali; R.R. Poznanski; K. Chaiwong; P. Yupapin (Results in Physics, 2018)
We have proposed a model of polariton generation, which is normally generated by the dipole and the strong coupling field interaction. This system consists of a gold grating embedded on the plasmonic island, which is embedded at the center of the nonlinear microring resonator, which is known as a panda-ring resonator. The strong coupling between the plasmonic waves and the grating can be formed by the whispering gallery mode (WGM) of light within a Panda-ring resonator, in which the output is a dipole-like particle known as a polariton and seen at the system output. By varying the energy of high-intensity laser pulse in the system and gold granting a strong field is generated at the output. A dipole is formed by a pair of the grating signals, where one propagates in the opposite direction of the other. By using suitable parameters, dipole-like signals can be generated. Theoretical formulation is performed for a two-level system and polariton oscillation frequency i.e., the Rabi frequency is plotted. The obtained ground and excited state frequencies of this two-level system are 187.86 and 198.20 THz, respectively.